Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/ppa.12802
|View full text |Cite
|
Sign up to set email alerts
|

Molecular breeding technologies and strategies for rust resistance in wheat (Triticum aestivum) for sustained food security

Abstract: Wheat is an important cereal food crop providing key nutrients to humankind. Rusts are the most destructive pathogens of cereal crops, with the exception of rice, across the world and resistant cultivars have been widely employed to reduce the yield losses caused by them. The modern intensive monoculture of cultivars and changing climatic conditions has created congenial conditions for the emergence of new virulent races such as Ug99, which is a great concern for world food security. Conventional breeding effo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 207 publications
(227 reference statements)
0
32
0
Order By: Relevance
“…Studies focused on Xiangmai 25 and Zhengmai 9023 have not identified genes for stripe rust resistance; however, they are presumed to contain unknown resistance genes based on field resistance evaluation ( Figure 4A). Combining these unknown resistance genes with the two QTL from P9897 can provide a long-lasting and high-level resistance to stripe rust [2]. For example, Xiangmai 25/P9897-34 has a higher resistance (IT = 0, DS = 0%) than the donor parents P9897 (IT = 2, DS = 10%), so we speculate that this line combines the unknown resistance genes from Xiangmai 25 with the two QTL from P9897.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Studies focused on Xiangmai 25 and Zhengmai 9023 have not identified genes for stripe rust resistance; however, they are presumed to contain unknown resistance genes based on field resistance evaluation ( Figure 4A). Combining these unknown resistance genes with the two QTL from P9897 can provide a long-lasting and high-level resistance to stripe rust [2]. For example, Xiangmai 25/P9897-34 has a higher resistance (IT = 0, DS = 0%) than the donor parents P9897 (IT = 2, DS = 10%), so we speculate that this line combines the unknown resistance genes from Xiangmai 25 with the two QTL from P9897.…”
Section: Discussionmentioning
confidence: 92%
“…It is planted in over 200 million hectares per year with a production of 751.1 million tons, and human consumption of wheat is increasing every year [1]. By 2050, the global population will exceed 9.5 billion, according to the World Bank, and global wheat production needs to increase by 60% to meet food demand [2,3]. Wheat stripe rust is caused by Puccinia striiformis f. sp.…”
Section: Introductionmentioning
confidence: 99%
“…Although, these genes are ineffective individually to the upcoming pathotypes of stem rust in India and elsewhere in the world, pyramided lines are expected to provide durable resistance against all the races. Agronomic performance of the improved lines was compared with the recipient parent [26].…”
Section: Wheat Rustsmentioning
confidence: 99%
“…However, the tolerance established in crops with conventional methods is usually not very robust or broad-spectrum [74]. Conventional selections are dependent upon several environmental variations and thus require a widespread location/generation field trial, delaying the progress of cultivar development [75]. As a general breeding criterion, 8-10 years of substantial breeding efforts are required to breed a cultivar right from the pre-breeding phase up to commercial release [76].…”
Section: Breeding Strategies For Low-cd Wheat Cultivarsmentioning
confidence: 99%